2013
DOI: 10.1108/intr-06-2012-0107
|View full text |Cite
|
Sign up to set email alerts
|

Online brand community response to negative brand events: the role of group eWOM

Abstract: PurposeBrand communities now play a significant role in building brand loyalty. Past researches focus on how brand community facilitates brand loyalty under normal market situations. Yet, limited research examines consumer responses to negative events within the brand community context. Drawing from social identity theory and the theory of involvement, the present study aims to reveal the role that group eWOM plays in influencing brand community members’ evaluation on negative brand decisions.Design/methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 78 publications
2
72
1
1
Order By: Relevance
“…Comparing to traditional mass media, in online media dealing with firm crisis such as online news forums, consumers can fill up their available pieces of information and no more restricted information quantity and associated information evaluation. Expanding previous studies on online discussion (Chang et al, 2013;Kaiser andBodendorf, 2012, Lee et al, 2006;Prabowo et al, 2008), the present studies suggest online-specific factor, the quantity of firm crisis-relevant information, by inspecting its moderating effects on consumers' regulatory focus.…”
Section: Discussionsupporting
confidence: 56%
“…Comparing to traditional mass media, in online media dealing with firm crisis such as online news forums, consumers can fill up their available pieces of information and no more restricted information quantity and associated information evaluation. Expanding previous studies on online discussion (Chang et al, 2013;Kaiser andBodendorf, 2012, Lee et al, 2006;Prabowo et al, 2008), the present studies suggest online-specific factor, the quantity of firm crisis-relevant information, by inspecting its moderating effects on consumers' regulatory focus.…”
Section: Discussionsupporting
confidence: 56%
“…Previous research on OBCs has focused attention on the identification of those characteristics that lead consumers to value brand communities and participate in communal activities (Stokburger-Sauer, 2010), the effect of this participation on brand identification and involvement (Chang et al, 2013), satisfaction with brands and brand loyalty (Stokburger-Sauer, 2010), or consumer engagement . Customers' participation in OBCs also affects performance measures, such as brand purchase (Steinman et al, 2015), new products success (Gruner et al, 2014), and sales (Adjei et al, 2010).…”
Section: Online Brand Communities (Obcs)mentioning
confidence: 99%
“…This seems particularly helpful when intending ads to be shared with other users in form of viral advertising (Liu-Thompkins 2013). Launching brand communities (Chang, Hsieh, and Tseng 2013) or brand pages (Muk 2013) can be appropriate ways to get in touch with customers drawing their attention to current advertising activities. Looking at the study's results, users indicated themselves to be rather likely to share advertisements since they greatly refer to UGC around advertising when looking for social interaction.…”
Section: Discussionmentioning
confidence: 99%